Ekonomi Berdaulat dan Berkeadilan dalam Perspektif Muhammad Iqbal - Abdullah Firdaus (INNOVATIO: Journal for Religious Innovation Studies, 2019)
Religion is the basic capital in building a solid economy. Social welfare in an Islamic perspective is not only oriented towards fulfilling material needs but must be based on the principle of justice which considers the aspects of material, social and spiritual satisfaction for the individual as well as for the wider community. This paper is intended to explore the thoughts and economic vision initiated by Muhammad Iqbal. This study is a qualitative study using a content-analysis approach through data taken from various writings related to this research. In the end, this research concludes that economic justice will be realized if there is political sovereignty, and political sovereignty will be realized if there is independence. The concept of a just economy is born from religious guidance and teachings because it directly defines the concept of holistic welfare in the vital aspects of human needs. Agama menjadi modal dasar dalam membangun perekonomian yang solid. Kesejahteraan sosial dalam perspektif Islam, tidak hanya berorientasi pada pemenuhan kebutuhan material saja akan tetapi ia harus berlandaskan kepada prinsip keadilan yang mempertimbangkan aspek kepuasan material, sosial dan spiritual bagi individu juga terhadap masyarakat luas. Tulisan ini dimaksudkan untuk mengeksplorasi pemikiran dan visi ekonomi yang digagas oleh Muhammad Iqbal. Kajian ini bersifat kualitatif dengan menggunakan pendekatan content-analysis melaui data-data yang diambil dari berbagai penulisan yang terkait dengan penelitian ini. Pada akhirnya penelitian ini menyimpulkan bahwa keadilan ekonomi akan terwujud jika ada kedaulatan politik, dan kedaulatan politik akan wujud jika ada kemerdekaan. Konsep ekonomi berkeadilan lahir sesungguhnya dari bimbingan dan ajaran agama karena ia secara langsung mendefinisikan konsep kesejahteran holistik aspek vital kebutuhan manusia.